Indonesia in the Making: Portraits of Customary Women in Perempuan Batih By A. R. Rizal: English - Nur Sapta Riskiawati; Nensia; Fauzi Razak; Absri (Universitas Islam Negeri Palopo, 2026)
This paper examines Perempuan Batih by A. R. Rizal within the framework of Indonesia in the making, positioning customary women as key subjects in the process of contemporary Indonesia’s social and cultural formation. Through representations of batih or nuclear family life, the text reveals that adat or customary norms do not operate as a fixed value system, but rather as a social practice that is continuously shaped, negotiated, and contested amid changing times. Employing approaches from the sociology of literature and feminist literary criticism, this paper analyzes value conflicts, gender relations, domestic labor, and shifts in authority within the domestic sphere as reflections of broader social dynamics. The analysis shows that women in Perempuan Batih are not merely portrayed as guardians of tradition, but also as agents of change who actively participate in the production of meaning surrounding adat. This paper argues that the text offers a critical reading of Indonesia as a process of becoming, in which women’s adat plays a significant role in shaping Indonesia’s present and future.